Requirements of cyclin a for mitosis are independent of its subcellular localization. - Dienemann, A.; Sprenger, F. (Current Biology, 2004)
Cyclin A (CycA), the only essential mitotic cyclin in Drosophila, is cytoplasmic during interphase and accumulates in the nucleus during prophase. We show that interphase localization is mediated by Leptomycin B (LMB)-sensitive nuclear export. This is a feature shared with human CyclinB1, and it is assumed that nuclear accumulation is necessary for mitotic entry. Here, we tested if the unique mitotic function of CycA requires nuclear accumulation. We fused subcellular localization signals to CycA and tested their mitotic capability. Surprisingly, nuclear accumulation was not required, and even a membrane-tethered form of CycA was able to induce mitosis. We noted that Cyclin B (CycB) protein disappears prematurely in CycA mutants, reminiscent of rca1 mutants. Rca1 is an inhibitor of Fizzy-related-APC/C activity, and in rca1 mutants, mitotic cyclins are degraded in G2 of the 16(th) embryonic cell cycle. Overexpression of Rca1 can restore mitosis in CycA mutants, indicating that the mitotic failure of CycA mutants is caused by premature activation of the APC/C. The essential mitotic function of CycA is therefore not the activation of numerous mitotic substrates by Cdk1-dependent phosphorylation. Rather, CycA-dependent kinase activity is required to inhibit one inhibitor of mitosis, the Fzr protein.